USM VC RECEIVES DELEGATION FROM UNIVERSITAS SYIAH KUALA, INDONESIA - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 6 March 2017 – The Universiti Sains Malaysia (USM) ViceChancellor, Professor Datuk Dr. Asma Ismail today received a courtesy visit from the delegation of Universitas Syiah Kuala (UNSYIAH), Indonesia which was led by its Rector, Professor Dr. Samsul Rizal.